2014
DOI: 10.4184/asj.2014.8.5.646
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Methods of Epidural Steroid Injection in the Treatment of Recurrent Lumbar Disc Herniation

Abstract: Study DesignProspective study.PurposeWe compared the effects of two methods of epidural steroid injection in patients with recurrent disc herniation.Overview of LiteratureTo our knowledge, there is no previous report of such a comparison in these patients.MethodsThe study was performed with 30 patients with relapsed lumbar disc herniation whose pain was not relieved by conservative remedies. The patients were divided into two groups, each of 15 patients, and entered the study for caudal or transforaminal injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…However, this treatment usually brings relatively large trauma to patients and may also damage the patient's spinal stability and induce complications. Thus, the application of this treatment is limited (2,3). How to reduce surgical trauma, maintain the integrity and stability of spine and reduce the incidence of postoperative complications is a difficult point for the treatment of lumbar disc herniation.…”
Section: Introductionmentioning
confidence: 99%
“…However, this treatment usually brings relatively large trauma to patients and may also damage the patient's spinal stability and induce complications. Thus, the application of this treatment is limited (2,3). How to reduce surgical trauma, maintain the integrity and stability of spine and reduce the incidence of postoperative complications is a difficult point for the treatment of lumbar disc herniation.…”
Section: Introductionmentioning
confidence: 99%
“…Three 30 , 32 , 37 of the 5 studies demonstrated that the TF groups experienced significantly better pain relief than the C groups. The remaining study 33 , 34 observed no difference between the 2 groups. Ackerman and Ahmad 2 observed better pain relief in the TF group at 24 weeks.…”
Section: Resultsmentioning
confidence: 88%
“…Galhom and al-Shatouri 32 reported that only 20% of the patients developed complications and that soreness at the injection site was the most common complication. Karamouzian et al 33 found that only 1 patient suffered temporary paraparesis in the C group. Mendoza-Lattes et al 29 did not observe the occurrence of complications; however, they reported that 10 of 39 patients required reinjection in the C group, in addition to 10 of 54 in the TF group.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We were recently interested by an article published in the Asian Spinal Journal by Karamouzian et al [ 1 ], entitled "Comparison of two methods of epidural steroid injection in the treatment of recurrent lumbar disc herniation". The authors presented an intriguing investigation comparing the effectiveness of the different methods of epidural steroid injection (ESI) in patients with recurrent lumbar disc herniation, and reported similar outcomes of transforaminal and caudal steroid injection procedures in the treatment of lumbar disc herniation.…”
mentioning
confidence: 99%